Participation Ladder in Business Incubation Program - Priyo Utomo; Arif Dharmawan; Zakariya Zakariya; Rudy Handoko (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The government's efforts in developing the economy of low-income communities in the city of Surabaya require high participation support. The low community participation in the incubation facilitation program for independent businesses is a problem that needs a solution Design/methodology/approach: The research method used is descriptive quantitative and case study methods. Data collection techniques using a questionnaire. The analysis technique uses inferential analysis and analysis of data characteristics. Findings: The results of this study indicate that the novelty at the level of community participation is arranged into three steps, namely: Stairs 1 (Basic Need Participation), 2 (Learning Encouragement), and 3 (Participation for growth). Paper type: Research paper